Utilizing principal agent and principal steward theories to assess the efficiacy of public private partnership in delivering black economic empowerment - Khatleli, Nthatisi (Department of Construction Economics and Management, 2014)
When the African National Congress (ANC) assumed power in 1994, its main economic policy was to overturn over three Hundred (300) years of black economic exclusivity which were intensified by the institutionalization of racism through Apartheid in 1948. The new dispensation adopted the policy of Affirmative Action which had been practiced in other parts of the world and contextualized it to South Africa through Black Economic Empowerment (BEE). The policy was designed to permeate every aspect of state and the private sector, especially companies which deal with government as providers of goods and services. The new government realized that because of former Apartheid privileges the established companies contain high specialist knowledge tacitness and management acumen, which would need to be utilised to benefit the new black-owned companies and assist in their development. Through the Targeted Procurement Policy the government compelled the established companies to unbundle their work packages to accommodate, small black-owned Affirmable Business Enterprises (ABEs) as sub-contractors or Joint Venture partners. This relationship between the government and the established companies is a typical Principal Agent (PA) relationship, and has quintessentially been beset with moral hazard and adverse selection problems militated by asymmetric information favoring the established companies. The identification of the construction industry as the flagship empowerment environment was due to its peculiarities of yielding more employment for a given capital flow and the low entrance barriers advocating for its amenability for a farreaching BEE inclusiveness. However, the opportunistic behaviours of established companies indicated through strategic misrepresentation of the true BEE beneficiaries has hampered the effectiveness of the BEE implementation. It is in this context that Public Private Partnerships (PPPs) were identified as a iv suitable vehicle to provide an incubatory environment to nurture the up-andcoming black owned Small, Medium and Micro Enterprises (SMMEs). This research uses PA theory to assess the efficacy of the PPPs in mitigating different forms of fronting which are indicative of opportunistic behaviours by established companies. The research also evaluates the effectiveness of the PPP environment in according ABEs access to complex and idiosyncratic information due to a PPP's longevity and strict monitoring regimen. A critical case is deployed in this study using the basic tenets of PA theory as lenses to study the behaviours of three major parties; the government, BEE beneficiaries and established companies. The limitations of Principal Agent theory are augmented by the introduction of Principal Steward (PS) theory to account for agent (established companies) post-contractual behavioural 'anomalies' not accommodated in the classic PA theory postulation. The observed bipolar agent character yields a new theory encompassing both the PA and PS theories demonstrative of a positive agent character transition akin to a Steward, which is yet intrinsically containing basic agent characteristics. This character transition is found to have been induced by robust PPP contractual arrangement, which in the end benefits BEE.